OUTBREAK OF SPRING VIRAEMIA OF CARP IN PRIVOLZHSKY FEDERAL DISTRICT IN 2014 - A. A. Pichueva; M. I. Doronin (Ветеринария сегодня)
Two isolates of spring viraemia of carp virus were detected when testing 30 samples of carp pathological material by virus isolation using EPC and FHM cell lines and by sandwich ELISA, IFA, leucocyte agglutination test, RT-PCR, and real time RT-PCR in the RF Privolzhsky Federal District in May 2014. Infectivity titres as well virus antigen concentration in carp pathological material were determined.